My Introspective Time Capsule - Michele Stafford-Levy (Networks: An Online Journal for Teacher Research, 2002)
This study takes place in the southwestern part of the United States on the Mexican-American border and is a narrative about a teacher's journey of self-discovery about her own teaching practices through reflection. Dr. Myriam Torres (New Mexico State University) and Michele Stafford-Levy ventured into the typical professor-student relationship. The professor guided her graduate student through a journey of self-discovery and how to document the process of self-reflection and action in her own classroom. By sharing these events from her professional life through autobiography, the student strives to serve as a model for both pre-service and in-service teachers to reflect, act, and document their journey of growth in their own practice.